Inflammatory Myofibroblastic Tumor of Spinal Canal: Brief Case Report - Bryl, Maciej; Fortuniak, Jan; Wiśniewski, Karol; Bobeff, Ernest Jan; Jin, Yizi; Papierz, Wielisław; Jaskólski, Dariusz Jan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
We describe a case of an intradural extramedullary inflammatory myofibroblastic tumor of the cervical spine. A 56-year-old woman presented with progressive neck pain, radiating to the right scapula, without any neurologic deficit. Magnetic resonance imaging showed an intradural extramedullary tumor with a dural tail sign, located at the C3–T1 segment with homogeneous contrast enhancement. The patient was operated on for a suspected meningioma. Pathologic examination showed fibrosis and inflammation with infiltration of B and T lymphocytes accompanied by plasmocytes, macrophages, and myofibroblast oocytes. We present the clinical course and review of the literature.
Keywords: inflammatory myofibroblastic tumor; spine tumor; meningioma; lymphoma